Cytological findings and risk factors for cervical lesions (Salud, Arte y Cuidado, 2024)
Objectives: to determine cervical pathologies in administrative and cleaner workers at the Universidad Centroccidental Lisandro Alvarado. Material and method: It has been made a descriptive cross-sectional investigation, with a non-probabilistic convenience sample, consisting of 95 women who underwent vaginal cytology whose analysis was through the Bethesda system 2014. Using a questionnaire-type instrument with closed questions was used with which the gynecological-obstetric history was investigated, taking into account the following study variables: age, family history, sexual debut, promiscuity, use of oral contraceptives (OCs), and cervical cytology screening. Results and conclusions: The following results were found: 20% within normal limits, 78.9% with benign cellular changes, of which reactive changes represented the highest prevalence at 82.7%, followed by infectious changes at 17.3%, with bacterial vaginosis present in all cases, and 1.1% with epithelial cell abnormalities. The risk factors with the highest prevalence for cervical lesions were: age between 35-55 years, found in 55.78% of patients, followed by the use of OCs for more than 5 years in 27.36% of cases, a family history of cervical cancer in 16.84%, and lastly, promiscuity represented 12.63% of the patients studied. Finally, with this study, the aim was to recognize and provide accurate information and statistical data to IPSTAUCLA and FUNSOUCLA, to promote prevention and avoid the progression of these pathologies, helping to reduce morbidity and mortality from this cause.
Keywords: cytology; risk factor; Cervical Cancer